Cahit Sıtkı Tarancı (Hayatı-Eserleri-Sanatı) / Enver Okur; Danışman Mustafa Özbalcı - Okur, Enver (Ondokuz Mayıs Üniversitesi, Sosyal Bilimler Enstitüsü, 1993)
Cahit Sıtkı Tarancı is one of the leading poets in Turkish literature of Contemporary Turkish literature ( Diyarbakır 1910 -Vienn 1956 ).He comes from the "Prinççizadeler " family in Diyarbakır . He is the first child of Arife Hanım and Bekir Sıtkı Bey coming from the same family . He started his primary education in Diyarbakır Nümune -i Terakki-i Hamidi Mekteb-i ibtidai'si and finished his primary education in the first part of Mektebi Sultani. For his secondary education ,he went to İstanbul (1924) . After studying at Kadıköy St .Joseph High School , he transferred to Galatasaray Lisesi and finished it in 1931. After Mülkiye Mektebi where studied for four years , he enrolled in Yüksek Ticaret Mektebi (High Trade School ) but the couldn't finish it. İn the same year when he started Ticaret Mektebi , he began to work for Sümerbank (1936) . İn late 1938 , he want to Paris and began to study in Ecole De Sciences Politiques . During the same time he was also a speaker in Turkish Broadcasts section of radio Paris. When the World War II broke out in 1940 , he returned home and joined the army in 1941 . When his military service was over , he started the work in his father's shop in İstanbul as an accountant. Then , he want to Ankara and worked for Anadolu Ajansı ( A news agency ), Toprak Mahsülleri Ofisi and Ministry of Labour as a trasnlator. He got married there on the 4th of April , 1951 . In 1954 he got seriously ill and as he could 't get better in Türkiye , he was sent to Vienn Austria on the 6th of September 1956. He died in the hospital in Vienna on the 12th of October ,1956. On the 26th of October ,1956, he was taken to Ankara and burried there in Cebeci Graveyard . His first involvement in poetry started during his school years in Saint Joseph and became more interested in it due to the encouragement of Ziya Osman Saba, who was his classmate in Galatasaray Lisesi ,and especially affter he had met Baudelaire ,poetry became an inevitable part of his life .His first poems were puplished in the magazines of " Servet-i Fünun " , " Akademi " and " Muhit " when hi was a student Galatasaray . In the folloving years , he puplished his works mainly in the magazines of " Varlık " " İnsan " , "Yücel ", "Kültür Haftası " and in " Cumhuriyet " which was he nevspaper . Being open to previous poets, perfection and baeuty were his only criteria, He didn't belong to any school of poetry and believing that Art is for Art , he creadet his own poems. His expertise at creating suitable form and contet , arrtistic ability in choosing and using the words , and his considering poetry the most important of all , his Iyricism , his sincerity his live language , and his clear and artistic style of writing have made him one of the most acceptable poets. In 1946 ,his popularity was highly increased after his poem ," Otuz Beş Yaş " ,was chosen the best in the contest organized by C.H.P.( Repuplician Populist Party ) . He wals also a poet passionate about the world with his feelings and way of life. He considered life to be as important as worship, It was the main principle of the society he belonged to to consider everythings as something voluable. He also didn't want to change beings by using " teşbih " ( a likening ) and " istiare " ( metaphor ) and the adorn the poem with the artistic game of words like his comtemporaries but he was satisfied with accepting the objects as how he perceived them. He's got a clear expression free from arts. The main features of his poems are his transferring the idioms coming from spoken language to the poems by modifing them, and changing the pauses in ordinary places in the poem to give it a freer way of expression . In his poems , besides the national and moral values , he dealt with the joy of living , death, love, nature, loneliness , drinking and longing for the past : Althoughhe wrote letters, articles and short stories , he is wery well know form his poems. His great success in poetry replaced his fame in prose.His works: Poems: 1. Ömrümde Sükût (1933) 2. Otuz Beş Yaş (1946) 3. Düşten Güzel(1952) 4. Sonrası (1957) . Letters : 1. Ziya'ya Mektuplar (Published by Ziya Osman Saba, 1957 ) 2. Evime ve Nihal'e Mektuplar ( Published by İnci Enginün , 1989) .Stories : 1. Cahit Sıtkı Tarancı'nın Hikayeciliği ve Hikayeleri published by Selahattin Önerli ,1976 ) .Bioqraphies : 1. Peyami Safa ( His life and works,1940).Translations: 1. Fransa'da Müstakil Resim ( from Adolphe Basler and Charles Kunstler) with the help of Ahmet Muhip Dranas ,1938. 2. Venedik'te ölüm, ( novel from Thomas Mann)
Tez (doktora) -- Ondokuz Mayıs Üniversitesi, 1993
Libra Kayıt No: 35340
Keywords: Tarancı; Cahit Sıtkı; 1910-1956 -- Eleştiri ve Yorum; TEZ DOK O41c